RENTANG WAKTU INSEMINASI BUATAN (IB) PADA TERNAK KERBAU - Budi Utomo; Iswanto; Fitri D.A; H. Kurnianto (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
The research was conducted from 2016 to 2018 “on farm research” involving members of livestock farmer groups. Research material for intensively reared buffalo, belonging to membersof a livestock farmer group in Sidamulya Village, Warureja District, Tegal Regency. Observation begins with buffalo that will be selected as research material. The research material depends on the condition of the livestock owned by the breeder, especially the availability of livestock that are included in the research criteria, namely adult female cattle in physiological status for a period of 2-3 months postpartum unestrous. Therefore, the research material is not observed simultaneously. The material of 24 adult female buffaloes was allocated into two timeframes for IB implementation, namely 11 IB at approximately 18 hours after showing signs of lust and 13 tails in IB after 36 hours showing signs of lust. There is no special treatment for livestock material, such as estrus synchronization. The variables observed were the presence of signs of estrus, the number of cattle that had been in IB and the time of IB implementation. IB was carried out twice (two straws). Observations on livestock showing signs of estrus were focused on the morning. The results of Hafez's research, reported that buffaloes were in lust between 18.00 and 06.00. The data obtained from the observations were analyzed descriptively. The results showed that the IB time in buffaloes should be done 36 hours, compared to 18 hours after the signs of estrus were known (69.23% ; 30.77%).